O impacto da deficiência auditiva na qualidade de vida do idoso, antes e um ano após a adaptação de próteses auditivas - Souza, Ruth Maria Magalhães Eringer de [UNIFESP] (2010)
The objective of this research was to study the effects of audiologic rehabilitation through hearing aids on quality of life of the elderly, according to gender and age. Method: The study included 50 elderly, 23 were female and 27 male. The patients were divided into two groups: Group 1 - includes 24 seniors, 11 females and 13 males aged 60 to 74 years and Group 2 (G2) - composed of 26 seniors, 12 females and 14 male, aged over 75 years. The patients were evaluated before the hearing aids fitting and a year after the adaptation of hearing aids, through questionnaires, HHIE and SF 36, and test MMSE. Bi-monthly follow-ups were conducted to ensure the effective use of hearing aids. Results: Analysis of HHIE revealed that the scores of the Emotional and Social Scales in the period after intervention were statistically significant in both age groups, both male and female. The test results showed that the MMSE scores in the period after intervention were statistically significant, and this difference was independent of sex and age. In SF 36, the results of six of the eight aspects studied showed statistically significant results in the post intervention, and functional ability, physical appearance, vitality, emotional aspects, social aspects and mental health. Aspects pain and general health showed no significant result in the post, however aspect pain in the elderly group 2 showed significant results in the post. Conclusion: There is little self-perception of participation restrictions after audiologic rehabilitation in the Social and Emotional Scales of HHIE. Elderly men have a greater self-perception of the restrictions on participation in the emotional aspect and social aspect, in the pre intervention. Elderly Group 2 have higher self-perception of the restriction of participation in the emotional aspect in the period before. The elderly showed better results in the MMSE test in the post regardless of sex and age. There is improvement in quality of life demonstrated in the aspects Functional Capacity, Physical, Vitality, Emotional, Social and Mental Health in the SF-36 questionnaire in the period after regardless of sex and age.